Antioksidantna i citotoksična aktivnost ekstrakta ploda štavelja (Rumex crispus L., Polygonaceae) - Ćebović, Tatjana; Jakovljević, Dunja; Maksimović, Zoran; Djordjevic, Snezana; Jakovljević, Sanja; Četojević-Simin, Dragana (Vojnosanitetski pregled, 2021)
Background/Aim. Rumex crispus (curly dock) is a wild perennial herbaceous plant, which products are considered as a rich source of biologically active molecules with antioxidant and cytotoxic activities. The aim of this study was to estimate of antioxidant and cytotoxic activities of aqueous extract of curly dock fruits. Methods. The aqueous extract of curly dock fruits was evaluated for its antioxidant activity by in vitro assays for ferric-reducing antioxidant power (FRAP), NO•, OH• and 2,2-diphenyl-1-picrylhydrazyl (DPPH)-free radical scavenging activities and the influence on lipid peroxidation in liposomes. The cytotoxicity of tested extract was examined in vitro in human cervix carcinoma (HeLa), colon adenocarcinoma (HT-29) and breast adenocarcinoma (MCF7) cells. Results. The tested extract showed a potential antioxidant activity manifested in scavenging of free radicals as well as an ability to decrease lipid peroxidation in liposomes. The results indicated tissue-selective cytotoxicity of R. crispus fruit extract in vitro. The most prominent antitumor activity was observed towards HeLa and MCF7 cell lines. Conclusion. The investigated aqueous fruit extract of R. crispus had potential antioxidant and cytotoxic activities, with necrosis as a main mechanism of induced cell-death. Different methods of extraction of R. crispus fruits, apart from aqueous, are recommended for further investigations.